2006
DOI: 10.1196/annals.1367.017
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin and Norepinephrine Reuptake Inhibition and Eating Behavior

Abstract: Brain neurotransmitters, serotonin and norepinephrine, play an important role in the central nervous control of energy balance and are involved in symptomatology related to both obesity and depression. Therefore both serotonin and norepinephrine neural pathways have been paid a special attention as targets for the antiobesity drugs, antidepressants, and drugs used in the treatment of eating disorders. Selective serotonin reuptake inhibitors (SSRI) have been used in the treatment of depression and eating disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
0
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 75 publications
1
57
0
6
Order By: Relevance
“…Furthermore, direct effects of the serotonergic system or an interaction with the HPA axis 64,65 could explain the interrelationship of MetS and MD. In fact, several studies indicate an interaction of glucocorticoids and TPH2 or its functional genetic variants, respectively.…”
Section: Tph2 and Risk For Mets In MDmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, direct effects of the serotonergic system or an interaction with the HPA axis 64,65 could explain the interrelationship of MetS and MD. In fact, several studies indicate an interaction of glucocorticoids and TPH2 or its functional genetic variants, respectively.…”
Section: Tph2 and Risk For Mets In MDmentioning
confidence: 99%
“…29,30,63 Furthermore, the serotonergic system has been shown to be involved in appetite and weight regulation and to modify the risk for metabolic disorders, as previous studies reported reduced CSF serotonin levels and decreased CNS serotonergic responsivity in MetS and obesity. 26,28 On the other hand, treatment with SSRIs decreases appetite and induces weight loss, 25,64 suggesting that dysregulation in central serotonergic system is important in obesity and MetS.…”
Section: Tph2 and Risk For Mets In MDmentioning
confidence: 99%
“…Comme tout bon médicament, les ISRS ne sont pas dépourvus d'effets secondaires. L'un d'entre eux est de provoquer une perte osseuse chez les patients traités au long cours, l'autre est d'augmenter l'appétit [16][17][18][19]. Ces observations cliniques suggèrent que la sérotonine d'origine cérébrale pouvait bien être un régulateur de la masse osseuse et de l'appétit.…”
Section: La Leptine Inhibe La Sérotonine Cérébraleunclassified
“…On the other hand, nontriclyclic agents, such as selective serotonin (SSRI) and serotonin-noradrenaline (SNRI) reuptake inhibitors, have been preferred for use in the treatment of anxiety and depression, but have failed to achieve sustained weight loss in the treatment of obesity (1,(13)(14)(15). Despite this, as with sibutramine, SSRIs and SNRIs have also increased locomotion (16,17).…”
mentioning
confidence: 99%
“…Thus, both neurotransmitter pathways have been given special attention as antiobesity and antidepressant agents (1).…”
mentioning
confidence: 99%